Identifying barriers and enablers to rigorous conduct and reporting of preclinical laboratory studies. - Manoj M Lalu; Justin Presseau; Madison K Foster; Victoria T Hunniford; Kelly D Cobey; Jamie C Brehaut; Carolina Ilkow; Joshua Montroy; Analyssa Cardenas; Ayni Sharif; Matthew S Jeffers; Dean A Fergusson (PLoS Biology, 2023)
Use of rigorous study design methods and transparent reporting in publications are 2 key strategies proposed to improve the reproducibility of preclinical research. Despite promotion of these practices by funders and journals, assessments suggest uptake is low in preclinical research. Thirty preclinical scientists were interviewed to better understand barriers and enablers to rigorous design and reporting. The interview guide was informed by the Theoretical Domains Framework, which is a framework used to understand determinants of current and desired behavior. Four global themes were identified; 2 reflecting enablers and 2 reflecting barriers. We found that basic scientists are highly motivated to apply the methods of rigorous design and reporting and perceive a number of benefits to their adoption (e.g., improved quality and reliability). However, there was varied awareness of the guidelines and in implementation of these practices. Researchers also noted that these guidelines can result in disadvantages, such as increased sample sizes, expenses, time, and can require several personnel to operationalize. Most researchers expressed additional resources such as personnel and education/training would better enable the application of some methods. Using existing guidance (Behaviour Change Wheel (BCW); Expert Recommendations for Implementing Change (ERIC) project implementation strategies), we mapped and coded our interview findings to identify potential interventions, policies, and implementation strategies to improve routine use of the guidelines by preclinical scientists. These findings will help inform specific strategies that may guide the development of programs and resources to improve experimental design and transparent reporting in preclinical research.